SISTEM PAKAR DIAGNOSA KERUSAKAN PADA HANDPHONE - Wahyu Taufik; Haryoko . (STMIK Mardira Indonesia, Bandung, 2015)
Problems that occur in life too complex or diverse, in this case needs to be examined carefully and thoroughly in finding the solution as well as in finding solutions to problems that occur on the mobile phone requires a software program application form in accordance with the problems that occur in the world business.An expert system is one of the data that can be used to assess any particular field of knowledge. With the system will be described real problem. Based on a special experience and is one of the alternatives to solve the problem.An expert system is an artificial intelligence that combines knowledge and data retrieval to solve problems normally requires human expertise. The purpose of the development of expert systems is actually not to replace the role of humans, but for substitution human knowledge in the form of the system, so it can be used by many people. Keywords: Mobile, Expert System, Diagnosis, Damage Abstrak Permasalahan yang terjadi di dalam kehidupan ini sangan kompleks atau beragam, dalam hal ini perlu di kaji dengan cermat dan teliti dalam mencari penyelesaiannya demikian juga dalam mencari solusi permasalahan yang terjadi pada handphone memerlukan suatu perangkat lunak yang berupa aplikasi program yang sesuai dengan permasalahan yang terjadi didunia usaha.Sistem pakar merupakan salah satu data yang dapat dipakai untuk mengkaji segala pengetahuan bidang tertentu. Dengan sistem itu akan dapat digambarkan masalah yang sebenarnya. Berdasarkan kepada pengalaman khusus dan merupakan salah satu aternatif untuk menyelesaikan masalah.Sistem pakar merupakan suatu kecerdasan buatan yang menggabungkan pengetahuan dan penelusuran data untuk memecahkan masalah secara normal memerlukan keahlian manusia. Tujuan dari pengembangan sistem pakar sebenarnya bukan untuk menggantikan peranan manusia, tetapi untuk mensubsitusikan pengetahuan manusia kedalam bentuk sistem, sehingga dapat digunakan oleh orang banyak. Kata Kunci: Handphone,Sistem Pakar, Diagnosa, Kerusakan